The Synaptic Vesicle Protein 2A Interacts With Key Pathogenic Factors in Alzheimer’s Disease: Implications for Treatment - Kong, Yanyan; Huang, Lin; Li, Weihao; Liu, Xuanting; Zhou, Yinping; Liu, Cuiping; Zhang, Shibo; Xie, Fang; Zhang, Zhengwei; Jiang, Donglang; Zhou, Weiyan; Ni, Ruiqing; et al. (Frontiers in Cell and Developmental Biology, 2021)
Alzheimer’s disease (AD), a serious neurodegenerative disease, is pathologically characterized by synaptic loss and dysfunction. Synaptic vesicle protein 2A (SV2A) is an indispensable vesicular protein specifically expressed in synapses and can be used as a biomarker for synaptic density. We found that the expression of SV2A was down-regulated in the hippocampus of AD patients, yet the relation of SV2A to other hallmarks of AD pathology such as amyloid precursor protein (APP), β-amyloid (Aβ), and Tau protein is not thoroughly clear. In addition, SV2A colocalized with APP and was down-regulated at Aβ deposition. Moreover, we found that SV2A deficiency leads to a simultaneous increase in Aβ and Tau hyperphosphorylation, while SV2A overexpression was associated with downregulation of β-site APP cleaving enzyme 1 and apolipoprotein E genes. In addition, evidence gained in the study points to the phosphatidylinositol 3-kinase signaling pathway as a possible mediator in SV2A regulation influencing the incidence and development of AD. With limited effective diagnostic methods for AD, a close interplay between SV2A and AD-related proteins demonstrated in our study may provide novel and innovative diagnostic and therapeutic opportunities.